Magnesium alloy wire reinforced degradable fiber composite rope knot and preparation and application thereof
Patent Information
- Application Number
- CN202311230170.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
Existing fiber temporary plugging agents have problems such as high cost, limited pressure bearing capacity, poor heat resistance and chemical stability in shale oil and gas exploitation.
Magnesium alloy wire is used to enhance the degradable fiber composite knot, and the mechanical properties and chemical stability are improved by weaving the magnesium alloy wire and degradable fiber into a composite knot.
It reduces the cost of temporary plugging agent, improves its pressure bearing capacity, heat resistance and chemical stability, broadens its application range in shale oil and gas mining, and improves the efficiency and success rate of joint-controlled fracturing.
Smart Images

Figure CN119684987A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnesium alloy wire reinforced degradable fiber composite knot and the preparation and application thereof. Background Art
[0002] The exploitation of shale oil and gas mainly relies on horizontal well fracturing technology. Temporary plugging agents are needed in the fracturing process. Temporary plugging agents commonly used in the fracturing transformation of complex fracture networks in unconventional reservoirs include temporary plugging balls mainly for temporary plugging of blastholes, conventional temporary plugging agents and fiber temporary plugging agents mainly for temporary plugging of fracture channels, and other new synthetic temporary plugging agents. In recent years, with the widespread application of multi-stage fracturing technology in horizontal wells in low-grade oil and gas reservoirs, the requirements for temporary plugging agents have become increasingly higher. Fiber for temporary plugging is a new type of temporary plugging agent that has advantages that other types of temporary plugging agents do not have. The fibers are often woven into knots for use. Therefore, optimizing fiber temporary plugging agents has become a necessity for fracturing production. However, fiber temporary plugging agents have disadvantages such as high price, limited pressure bearing capacity, poor heat resistance and chemical stability. Summary of the invention
[0003] The present invention is made in order to reduce the cost of the degradable fiber composite knot, improve its pressure bearing capacity, heat resistance and chemical stability, and broaden its scope of use. The present invention is used for temporary plugging of steering fracturing to improve the efficiency and success rate of fracture-controlled fracturing.
[0004] As a first aspect of the present invention, it relates to a magnesium alloy wire reinforced degradable fiber composite knot, which comprises degradable fiber and magnesium alloy wire, and the mass ratio of the degradable fiber to the magnesium alloy wire is 2-9:1-8.
[0005] In one or some optional embodiments, the degradable fiber is PGA fiber.
[0006] In one or some optional embodiments, the magnesium alloy is a Mg-Li alloy, a Mg-Li-Al-Cu alloy, a Mg-Li-Ni alloy or a Mg-Li-Cu alloy.
[0007] In one or some optional embodiments, the weight percentage of Li in the Mg-Li alloy is 4-14.0%, and the balance is Mg.
[0008] In one or some optional embodiments, the weight percentage of Li in the Mg-Li-Al-Cu alloy is 4-14.0%, the weight percentage of Cu is 0.2-5.0%, the weight percentage of Al is 1.0-9.0%, the weight percentage of Ni is 0.3-6.0%, and the balance is Mg.
[0009] In one or some optional embodiments, the weight percentage of Li in the Mg-Li-Ni alloy is 4-14.0%, the weight percentage of Ni is 0.3-6.0%, and the balance is Mg.
[0010] In one or some optional embodiments, the weight percentage of Li in the Mg—Li—Cu alloy is 4-14.0%, the weight percentage of Cu is 0.2-5.0%, and the balance is Mg.
[0011] In one or some optional embodiments, the diameter of the magnesium alloy wire is 0.05-3 mm.
[0012] In one or some optional embodiments, the diameter of the magnesium alloy wire reinforced degradable fiber composite knot is 4-40 mm.
[0013] In one or some preferred embodiments, the diameter of the magnesium alloy wire reinforced degradable fiber composite knot is 5-30 mm, and more preferably 10-25 mm.
[0014] As a second aspect of the present invention, it relates to a method for preparing the above-mentioned magnesium alloy wire reinforced degradable fiber composite knot, the method comprising:
[0015] Preparation of magnesium alloy wire: After mixing magnesium ingots with other metal materials, smelting and casting into magnesium alloy ingots, homogenizing the magnesium alloy ingots, and then performing multiple hot extrusions into magnesium alloy rods, and drawing and deforming the rods to obtain magnesium alloy wires;
[0016] Preparation of composite knots: twisting the degradable fibers into degradable fiber threads, mixing the magnesium alloy wires and the degradable fiber threads and weaving them into composite thin ropes, and then forming magnesium alloy wire-reinforced degradable fiber composite knots through a weaving and knotting method.
[0017] In one or some preferred embodiments, the other metal material is at least one of a lithium ingot, an aluminum ingot, a Mg-Ni master alloy or a Mg-Cu master alloy.
[0018] As a third aspect of the present invention, it relates to the application of the above-mentioned magnesium alloy wire reinforced degradable fiber composite knot in oil field exploitation.
[0019] The magnesium alloy wire reinforced degradable fiber composite knot provided by the present invention uses the magnesium alloy wire to replace part of the degradable fiber, which can reduce the cost and improve the heat resistance and chemical stability.
[0020] The magnesium alloy wire used in the present invention is relatively simple to prepare and obtain, and Li, Al, Cu, Ni, etc. are used as alloying elements, which will not cause great damage to the formation after dissolution. Mg-Li alloy is the lightest metal structural material at present, and the addition of Li can change the crystal structure. When the Li content is higher than 5.7%, the Li element is dissolved in the Mg metal to form a single-phase solid solution α-Mg; when the Li content is higher than 10.3%, the Mg element is dissolved in the Li metal to form a single-phase solid solution β-Li; when the Li content is 5.7-10.3%, a two-phase structure α-Mg phase + β-Li phase is formed. Since the BCC body-centered cubic structure is better than the HCP close-packed hexagonal structure, the plasticity of the magnesium alloy will increase with the increase of Li content. Li has a more negative electrode potential than Mg, and alloying Li will aggravate the corrosion of the Mg matrix. There is a potential difference between the α-Mg phase and the β-Li phase, forming a galvanic pair and galvanic corrosion between them, resulting in the β-Li phase being preferentially corroded as the anode. Al, an element with high solid solubility in magnesium-lithium alloy, dissolves into Mg-Li alloy to generate phases such as MgLi2Al, AlxLi, Mg5Zn, and MgLi2Zn. The MgLi matrix will experience severe lattice distortion, increase the resistance to dislocation movement, hinder dislocation movement, and play a role in solid solution strengthening. Cu has very low solubility in α-Mg phase and is almost insoluble in β-Li phase. Adding Cu to the alloy can generate AlCuMg phase and reduce the corrosion resistance of magnesium-lithium alloy. Ni has very low solubility in α-Mg phase and is almost insoluble in β-Li phase. Adding Ni to the alloy can generate Mg2Ni phase and reduce the corrosion resistance of magnesium alloy.
[0021] The magnesium alloy wire reinforced degradable fiber composite knot provided by the present invention has excellent comprehensive properties such as mechanics and corrosion. The tensile strength of the magnesium alloy wire suitable for shale oil and gas exploitation is ≥70MPa, and the elongation is greater than 10%. By adjusting the composition of the magnesium alloy wire and the ratio of the magnesium alloy wire and the fiber, the mechanical properties and dissolution rate of the temporary plugging knot can be adjusted to meet the application requirements in different environments: the use environment of the magnesium alloy wire reinforced degradable fiber composite knot is an underground mineralization degree of 1000 to 30000, the applicable underground temperature is between 40-200℃, the dissolution time is between 8-100 hours, and under different application conditions, its degradation rate can vary in a wide range, and the degradation rate is 0.1-60mg / cm 2 / h. The magnesium alloy wire reinforced degradable fiber composite knot is applied to temporary plugging of diverting fracturing, which can improve the efficiency and success rate of fracture-controlled fracturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a photo of the appearance of the magnesium alloy wire prepared by the present invention;
[0023] Figure 2 XRD patterns of drawn and annealed Mg-14Li alloy wires;
[0024] Figure 3 The impedance spectrum of Mg-14Li alloy wire in 93℃ / 3% KCl solution;
[0025] Figure 4 This is the mechanical properties test diagram of Mg-14Li alloy wire. DETAILED DESCRIPTION
[0026] The following is a detailed description of the embodiments of the present invention: The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters for which specific conditions are not specified in the following embodiments are generally based on conventional conditions.
[0027] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0028] The inventors implemented the relevant technical solutions with reference to the patent CN110106416B "A super-high strength soluble magnesium alloy and its preparation method and application", and found that the tensile strength of the alloy obtained by the method after heat treatment and deformation process exceeds 520MPa, the yield strength exceeds 440MPa, and the elongation is 5.5-6.5%. The inventors implemented the relevant technical solutions with reference to the patent CN110184518A "A fast-dissolving high-strength and high-elongation magnesium alloy and its preparation method", and found that the alloy prepared by the method can react and dissolve quickly with water, and has a high tensile strength greater than 220MPa and an elongation between 16-30%. The inventors implemented the relevant technical solutions with reference to the patent CN110923531B "A low-cost high-plasticity soluble magnesium alloy material and its preparation method", and found that the room temperature tensile strength of the soluble magnesium alloy prepared by the method is 286MPa, the yield strength is 184MPa, and the elongation is 15.1%. The inventors implemented the relevant technical scheme with reference to patent CN112921223B "A Fe-containing soluble magnesium alloy and its preparation method", and found that the soluble magnesium alloy prepared by this method has a tensile strength of 260-380MPa and an elongation of 14-30%. The soluble magnesium alloy of the above patent invention has high strength but low elongation.
[0029] The inventors implemented the relevant technical solutions with reference to CN113150757A "A high-strength, degradable, flexible knotted blasthole temporary plugging agent and its preparation method and application", and found that the temporary plugging knot products prepared by this method are all made of pure fiber weaving and processing, and the deformability of the temporary plugging fiber rope is affected by the fiber weaving process, weaving structure and the size of the temporary plugging knot. The production and processing and product quality stability are not high; the degree of deformation is limited, and the pressure bearing strength is low. The inventors implemented the relevant technical solutions with reference to patent CN113201855B "A fully degradable high-strength knotted temporary plugging agent", and found that the temporary plugging is made of pure fiber and has the advantage of being able to be completely degraded, but the strength of the knot is low, the deformation is small, and the plugging effect on irregular holes is poor. The inventors implemented the relevant technical solutions with reference to patent CN115612468A "A knot temporary blocking ball and its preparation method", and found that the knot temporary blocking ball includes a knot ball and a water-soluble packaging shell layer that wraps the knot ball, and the applicable temperature of the temporary blocking ball is 60-150°C. The inventors implemented the relevant technical solutions with reference to patent CN115109572A "A high-strength, deformable and degradable knot temporary blocking ball and its preparation method and application", and found that the temporary blocking ball is composed of an elastic ball and a composite fiber rope that radially penetrates the elastic ball, and the applicable temperature range of the temporary blocking ball is 50-130°C. In summary, the deformability of the temporary blocking fiber rope is affected by the fiber weaving process, weaving structure and the size of the temporary blocking knot, and the production and processing and product quality stability are not high; the degree of deformation is limited, and the pressure bearing strength is low; the applicable temperature window of the above two types of temporary blocking balls is narrow.
[0030] Since the above methods did not meet the inventor's expectations, the inventor made the present invention after further research and development.
[0031] Example 1
[0032] Mg-14Li alloy / PGA composite knot
[0033] The required alloy components are weighed in a weight percentage ratio of 14wt.% Li and the balance Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, and the purity of the lithium ingot is greater than or equal to 99.99%.
[0034] After the surface of the raw materials is polished clean, the magnesium ingot is heated and melted in a high-purity graphite crucible. Under the protection of high-purity SF6 and CO2 gases, the remaining raw materials are added one by one. After heating to 730-750℃ and keeping warm for 15-30 minutes, the temperature is lowered to 700-720℃ for casting. The casting mold uses a water-cooled steel mold.
[0035] The ingot is then homogenized at a holding temperature of 230°C for 5.5 hours and then air-cooled. The homogenized ingot is descaled and processed into a cylinder, which is then extruded. The extrusion temperature is 220°C, the extrusion speed is 0.2-0.4 mm / s, and the extrusion ratio is 23.4.
[0036] Annealing at 280℃ / 15min before drawing, then the rod is subjected to drawing deformation treatment, and the drawing speed is 4m / min. After 5 drawing passes, stress relief annealing treatment is performed, the annealing temperature is 180-220℃, and the annealing time is 10-15min. After the drawing is completed, annealing is performed at 200℃ / 30min. Finally, Mg-14Li alloy wire with a diameter of 0.2mm is obtained.
[0037] The biodegradable fibers are twisted into threads, and the Mg-14Li alloy wires and the biodegradable fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0038] The XRD patterns of the Mg-14Li alloy wire in the drawn and annealed states prepared in this embodiment are as follows: Figure 2 As shown by Figure 2 It can be seen that after drawing, the Mg-14Li alloy phase is β-Li phase, and a small amount of α-Mg phase appears; after annealing, the intensity of the diffraction peak has no obvious change. Its impedance spectrum in 93℃ / 3% KCl solution is shown in Figure 3 As shown by Figure 3 It can be seen that the corrosion rate of Mg-14Li alloy wire in 93℃ / 3% KCl solution is 1.2 mg / cm 2 / h. Its mechanical properties test diagram is as follows Figure 4 As shown by Figure 4 It can be seen that the tensile strength of the Mg-14Li alloy wire in the drawn state is 125.73MPa, and the elongation is 15.48%; the tensile strength of the annealed alloy is 81.17MPa, and the elongation is 25.68%.
[0039] Example 2
[0040] Mg-4Li / PGA composite knot
[0041] The required alloy components are weighed in a weight percentage ratio of 4wt.% Li and the balance being Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, and the purity of the lithium ingot is greater than or equal to 99.99%.
[0042] After the surface of the raw materials is polished clean, the magnesium ingot is heated and melted in a high-purity graphite crucible. Under the protection of high-purity SF6 and CO2 gases, the remaining raw materials are added one by one. After heating to 730-750℃ and keeping warm for 15-30 minutes, the temperature is lowered to 700-720℃ for casting. The casting mold uses a water-cooled steel mold.
[0043] The ingot is then homogenized at a holding temperature of 230°C for 5.5 hours and then air-cooled. The homogenized ingot is descaled and processed into a cylinder, which is then extruded. The extrusion temperature is 220°C, the extrusion speed is 0.2-0.4 mm / s, and the extrusion ratio is 23.4.
[0044] Annealing at 280℃ / 15min before drawing, then the rod is subjected to drawing deformation treatment, and the drawing speed is 4m / min. After 5 drawing passes, stress relief annealing treatment is performed, the annealing temperature is 180-220℃, and the annealing time is 10-15min. After the drawing is completed, annealing is performed at 200℃ / 30min. Finally, Mg-4Li alloy wire with a diameter of 0.2mm is obtained.
[0045] The PGA fibers are twisted, and the Mg-4Li alloy wires and the PGA fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0046] The test results show that the tensile strength of the Mg-4Li alloy wire prepared in this embodiment is 126.67 MPa, the elongation is 15.2%, and the corrosion rate in 93°C / 3% KCl solution is 0.8 mg / cm 2 / h.
[0047] Example 3
[0048] Mg-8Li / PGA composite knot
[0049] The required alloy components are weighed according to the weight percentage of 4wt.% Li and the balance is Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, and the purity of the lithium ingot is greater than or equal to 99.99%. After the surface of the raw materials is polished clean, the magnesium ingot is heated and melted in a high-purity graphite crucible, and the remaining raw materials are added one by one under the protection of SF6 and CO2 high-purity gases, and the temperature is raised to 730-750℃, and then kept warm for 15-30min, and then cooled to 700-720℃ for casting. The casting mold adopts a water-cooled steel mold.
[0050] The ingot is then homogenized at a holding temperature of 230°C for 5.5 hours and then air-cooled. The homogenized ingot is descaled and processed into a cylinder, which is then extruded. The extrusion temperature is 220°C, the extrusion speed is 0.2-0.4 mm / s, and the extrusion ratio is 23.4.
[0051] Annealing at 280℃ / 15min before drawing, then the rod is subjected to drawing deformation treatment, and the drawing speed is 4m / min. After 5 drawing passes, stress relief annealing treatment is performed, the annealing temperature is 180-220℃, and the annealing time is 10-15min. After the drawing is completed, annealing at 200℃ / 30min is performed. Finally, Mg-8Li alloy wire with a diameter of 0.2mm is obtained.
[0052] The PGA fibers are twisted, and the Mg-8Li alloy wires and the PGA fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0053] The test results show that the tensile strength of the Mg-8Li alloy wire prepared in this embodiment is 102.03 MPa, the elongation is 20.54%, and the corrosion rate in 93°C / 3% KCl solution is 1.1 mg / cm 2 / h.
[0054] Example 4
[0055] Mg-14Li-1Al-0.5Cu / PGA composite knot
[0056] The required alloy components are weighed according to the weight percentage of 14wt.% Li, 0.5wt.% Cu, 1.0wt.% Al, and the balance is Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, the purity of the lithium ingot and the aluminum ingot is greater than or equal to 99.99%, and the purity of the Mg-Cu master alloy is greater than or equal to 99.99%. After the surface of the raw materials is polished clean, the magnesium ingot is heated and melted in a high-purity graphite crucible, and the remaining raw materials are added one by one under the protection of SF6 and CO2 high-purity gases, and the temperature is raised to 730-750℃, and then kept warm for 15-30min, and then cooled to 700-720℃ for casting, and the casting mold adopts a water-cooled steel mold.
[0057] After the surface of the raw material is polished clean, the magnesium ingot is melted in a high-purity graphite crucible. Under the protection of high-purity SF6 and CO2 gases, the remaining ingredients are added one by one. The temperature is raised to 750°C and kept warm for 20 minutes. Then the temperature is lowered to 710°C for casting. The casting mold uses a water-cooled steel mold.
[0058] The ingot was then homogenized at a holding temperature of 450°C for 24 hours and then air-cooled. The homogenized ingot was descaled and processed into a cylinder, which was then extruded. The extrusion temperature was 380°C, the extrusion speed was 2 mm / s, and the extrusion ratio was 25.
[0059] Annealing was performed at 270℃ / 15min before drawing, the drawing speed was 3m / min, stress relief annealing was performed after every 2 drawing passes, the annealing temperature was 270℃ / 10min, and annealing was performed at 270℃ / 30min after drawing. Finally, Mg-14Li-1Al-0.5Cu alloy wire with a diameter of 0.2mm was obtained.
[0060] The PGA fibers are twisted, and the Mg-14Li-1Al-0.5Cu alloy wires and the PGA fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0061] The test results show that the tensile strength of the Mg-14Li-1Al-0.5Cu alloy wire prepared in this embodiment is 126.56MPa, the elongation is 22.35%, and the corrosion rate in 93℃ / 3% KCl solution is 4.54mg / cm 2 / h.
[0062] Example 5
[0063] Mg-4Li-0.3Ni / PGA composite knot
[0064] The required alloy components are weighed according to the weight percentage of 4wt.% Li, 0.3wt.% Ni, and the balance Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, the purity of the lithium ingot is greater than or equal to 99.99%, and the purity of the Mg-Ni master alloy is greater than or equal to 99.99%.
[0065] After the surface of the raw material is polished clean, the magnesium ingot is melted in a high-purity graphite crucible. Under the protection of high-purity SF6 and CO2 gases, the remaining ingredients are added one by one. The temperature is raised to 750°C and kept warm for 20 minutes. Then the temperature is lowered to 710°C for casting. The casting mold uses a water-cooled steel mold.
[0066] The ingot was then homogenized at a holding temperature of 450°C for 24 hours and then air-cooled. The homogenized ingot was descaled and processed into a cylinder, which was then extruded at a temperature of 330°C, a speed of 1 mm / s, and an extrusion ratio of 28.
[0067] Annealing was performed at 250°C / 15min before drawing, the drawing speed was 3m / min, stress relief annealing was performed after every 3 drawing passes, the annealing temperature was 250°C / 10min, and annealing was performed at 250°C / 30min after drawing. Finally, Mg-4Li-0.3Ni alloy wire with a diameter of 0.2mm was obtained.
[0068] The PGA fibers are twisted, and the Mg-4Li-0.3Ni alloy wires and the PGA fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0069] The test results show that the tensile strength of the Mg-4Li-0.3Ni alloy wire prepared in this embodiment is 93.78 MPa, the elongation is 17.86%, and the corrosion rate in 93°C / 3% KCl solution is 2.05 mg / cm 2 / h.
[0070] Example 6
[0071] Mg-8Li-0.2Cu / PGA composite knot
[0072] The required alloy components are weighed according to the weight ratio of 8wt / % Li, 0.2wt% Cu, and the balance Mg, wherein the purity of the magnesium ingot is greater than or equal to 99.99%, the purity of the lithium ingot is greater than or equal to 99.99%, and the purity of the Mg-Cu master alloy is greater than or equal to 99.99%.
[0073] After the surface of the raw material is polished clean, the magnesium ingot is melted in a high-purity graphite crucible. Under the protection of high-purity SF6 and CO2 gases, the remaining ingredients are added one by one. The temperature is raised to 750°C and kept warm for 20 minutes. Then the temperature is lowered to 710°C for casting. The casting mold uses a water-cooled steel mold.
[0074] The ingot was then homogenized at a holding temperature of 450°C for 24 hours and then air-cooled. The homogenized ingot was descaled and processed into a cylinder, which was then extruded at a temperature of 330°C, a speed of 1 mm / s, and an extrusion ratio of 28.
[0075] Annealing was performed at 280°C / 15min before drawing, the drawing speed was 3m / min, stress relief annealing was performed after every 3 drawing passes, the annealing temperature was 280°C / 10min, and annealing was performed at 280°C / 30min after drawing. Finally, Mg-8Li-0.2Cu alloy wire with a diameter of 0.2mm was obtained.
[0076] The PGA fibers are twisted, and the Mg-8Li-0.2Cu alloy wires and the PGA fibers are woven into a composite fiber knot with a diameter of 5-30 mm.
[0077] The test results show that the tensile strength of the Mg-8Li-0.2Cu alloy wire prepared in this embodiment is 98.87MPa, the elongation is 23.36%, and the corrosion rate in 93℃ / 3% KCl solution is 2.6mg / cm 2 / h.
[0078] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.
Claims
1. A magnesium alloy wire reinforced degradable fiber composite knot, characterized in that: The magnesium alloy wire reinforced degradable fiber composite knot comprises degradable fiber and magnesium alloy wire, and the mass ratio of the degradable fiber to the magnesium alloy wire is 2-9:1-8.
2. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 1, characterized in that: The degradable fiber is PGA fiber.
3. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 1, characterized in that: The magnesium alloy is a Mg-Li alloy, a Mg-Li-Al-Cu alloy, a Mg-Li-Ni alloy or a Mg-Li-Cu alloy.
4. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 3, characterized in that: The weight percentage of Li in the Mg-Li alloy is 4-14.0%, and the balance is Mg.
5. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 3, characterized in that: The weight percentage of Li in the Mg-Li-Al-Cu alloy is 4-14.0%, the weight percentage of Cu is 0.2-5.0%, the weight percentage of Al is 1.0-9.0%, the weight percentage of Ni is 0.3-6.0%, and the balance is Mg.
6. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 3, characterized in that: The weight percentage of Li in the Mg-Li-Ni alloy is 4-14.0%, the weight percentage of Ni is 0.3-6.0%, and the balance is Mg.
7. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 3, characterized in that: The weight percentage of Li in the Mg-Li-Cu alloy is 4-14.0%, the weight percentage of Cu is 0.2-5.0%, and the balance is Mg.
8. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 1, characterized in that: The diameter of the magnesium alloy wire is 0.05-3 mm.
9. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 1, characterized in that: The diameter of the magnesium alloy wire reinforced degradable fiber composite knot is 4-40 mm.
10. The magnesium alloy wire reinforced degradable fiber composite knot according to claim 9, characterized in that: The diameter of the magnesium alloy wire reinforced degradable fiber composite knot is 5-30 mm, and more preferably 10-25 mm.
11. A method for preparing the magnesium alloy wire reinforced degradable fiber composite knot according to any one of claims 1 to 10, characterized in that: The method comprises: Preparation of magnesium alloy wire: After mixing magnesium ingots with other metal materials, smelting and casting into magnesium alloy ingots, homogenizing the magnesium alloy ingots, and then performing multiple hot extrusions into magnesium alloy rods, and drawing and deforming the rods to obtain magnesium alloy wires; Preparation of composite knots: twisting the degradable fibers into degradable fiber threads, mixing the magnesium alloy wires and the degradable fiber threads and weaving them into composite thin ropes, and then forming magnesium alloy wire-reinforced degradable fiber composite knots through a weaving and knotting method.
12. The method according to claim 1, characterized in that The other metal material is at least one of a lithium ingot, an aluminum ingot, a Mg-Ni master alloy or a Mg-Cu master alloy.
13. Use of the magnesium alloy wire reinforced degradable fiber composite knot according to any one of claims 1 to 10 in oil field exploitation.
Citation Information
Patent Citations
A high-strength soluble magnesium alloy, its preparation method and application
CN110106416B
High-strength and high-ductility magnesium alloy capable of being dissolved rapidly and preparation method thereof
CN110184518A
A low-cost, high-plasticity soluble magnesium alloy material and its preparation method
CN110923531B
A Fe-containing soluble magnesium alloy and its preparation method
CN112921223B
A fully degradable high-strength knot temporary plug
CN113201855B